2021
DOI: 10.1109/tbme.2020.3003131
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Air Management in CT Power Injections: A Comprehensive Approach to Reducing Air Embolization

Abstract: Venous air embolism as a complication of contrast media administration from power injection systems in CT is found to occur in 7%-55% of patients, impacting patient safety, diagnostic image quality, workflow efficiency, and patient and radiographer satisfaction. This study reviews the challenges associated with reactive air management approaches employed on contemporary systems, proposes a novel air management approach using proactive methods, and compares the impact of reactive and proactive approaches on inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…All the studies were identified by the literature search (PubMed), and according to selection criteria, 5 classic papers were included: case series from 1987 7 , original with 23 patients from 1988 17 , original with 79 patients from 1997 12 , one review 18 from 1992 that included experimental (animal) data, case reports, case series, and clinical investigations and a review from 1997 8 ; also 17 papers were considered in this systematic review: review article 5 , 9 were case reports 6,9,13,19-24 , technical 14 , technical/procedure 4,15 , technical/comparative analysis 25 , observational study 10 ; originals with 14 patients 11 and other with 100 cases 4 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the studies were identified by the literature search (PubMed), and according to selection criteria, 5 classic papers were included: case series from 1987 7 , original with 23 patients from 1988 17 , original with 79 patients from 1997 12 , one review 18 from 1992 that included experimental (animal) data, case reports, case series, and clinical investigations and a review from 1997 8 ; also 17 papers were considered in this systematic review: review article 5 , 9 were case reports 6,9,13,19-24 , technical 14 , technical/procedure 4,15 , technical/comparative analysis 25 , observational study 10 ; originals with 14 patients 11 and other with 100 cases 4 .…”
Section: Resultsmentioning
confidence: 99%
“…McDermott MC et al 25 reviews the challenges associated with reactive air management approaches employed on contemporary systems, proposes a novel air management approach using proactive methods, and compares the impact of reactive and proactive approaches on injected air volumes under simulated clinical use. The results indicate that the use of a proactive approach could significantly reduce the prevalence of observable, and potentially artifact-inducing, VAE in CECT procedures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although clinical studies with patients remain the criterion standard, researchers have made use of preclinical evaluation tools to understand underlying physiological principles, as well as advancing clinical understanding and knowledge while avoiding unnecessary radiation exposure to patients. These tools include benchtop engineering test setups, computer modeling software, radiation dose phantoms, animal models, and dynamic flow circulation phantoms 13–18 . Over the past 2 decades, the dynamic flow circulation phantoms have been used in evaluation and optimization of contrast-enhanced CT procedures.…”
mentioning
confidence: 99%
“…These tools include benchtop engineering test setups, computer modeling software, radiation dose phantoms, animal models, and dynamic flow circulation phantoms. [13][14][15][16][17][18] Over the past 2 decades, the dynamic flow circulation phantoms have been used in evaluation and optimization of contrast-enhanced CT procedures. These circulation phantoms are intended to represent the dynamic blood flow within a human cardiovascular system and provide a stable testing platform allowing for high levels of standardization and reduced variability.…”
mentioning
confidence: 99%